Effect of Varietal Differences and Nixtamalization Conditions on the Textural, Rheological, and Nutritional Properties of Corn (Zea mays)–Based Masa Flour: Kassaï and Atp-Y Corn Varieties - Hygride Dongmo; Gires Teboukeu Boungo; Hermann Arantes Kohole Foffe; Marie Madeleine Nanga Ndjang; Bruno Fotso Saah; Saturnin Naïm; Jean de Dieu Tamokou; Klang Mathilde Julie (Journal of Food Quality)
Nixtamalization is a process used in the production of tortillas. This process offers many advantages, such as improving the rheological, nutritional, and textural properties of the masa. This process is carried out under different steps which affect the quality of the final product such as the cooking and soaking conditions and the quantity of ash. In addition, the fragility of the masa makes the tortillas brittle. The present work was initiated with the aim of determining the nixtamalization conditions that would improve the textural, rheological, and nutritional properties of masa. The response surface methodology, using the central composite design was applied to three factors including the ash content and cooking and soaking times, and the responses evaluated were the adhesiveness, cohesion, final viscosity, and gelatinization temperature of masa obtained from two varieties of maize (Atp-Y and Kassaï). The optimums masa flours obtained were characterized using standard methods. Results showed that, the masa made from Kassaï variety needed a cooking time of 51.21 min and soaking time of 16.10 h in the presence of 0.80 g of ash. For the Atp-Y variety, the conditions included a cooking time of 49.17 min and a soaking time of 23.4 h in the presence of 0.24 g of ash. The responses obtained showed an adhesiveness of 0.10 kg/f and 0.05 kg/f, cohesion of 1.08 kg/f and 1.23 kg/f, final viscosity of 1504.80 cP and 1328.30 cP, gelatinization temperature 73.50 °C and 71.50 °C, and finally retrogradation 435.50 cP and 316 cP, respectively, for Kassaï and Atp-Y. Chemical characterization of the optimum masa showed that the white masa had a high protein content (10.50%), carbohydrates (71.70%), and fiber (2%) while the yellow masa presented the highest lipid content (5.47%). These finding demonstrated that Kassaï (white) maize-masa flour obtained in optimal conditions can be recommended for the production of good quality tortillas because tortillas made with this masa are less crumbly and more elastic.